2022
DOI: 10.1002/npr2.12226
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of oral administration of a medium‐chain fatty acid, capric acid, on locomotor activity and anxiety‐like and depression‐related behaviors in adult male C57BL/6J mice

Abstract: Aim Capric acid (also known as decanoic acid or C10) is one of the fatty acids in the medium‐chain triglycerides (MCTs) commonly found in dietary fats. Although dietary treatment with MCTs is recently of great interest for the potential therapeutic effects on neuropsychiatric disorders, the effects of oral administration of C10 on behavior remain to be examined. This study investigated acute and chronic effects of oral administration of C10 on locomotor activity and anxiety‐like and depression‐related behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…There was no difference between the MCT group and the control group for the forced swim test or the social exploration test [ 62 ]. A recent study found that the acute administration of a high dose of decanoic acid increased depression/anxiety in mice during the forced swim test [ 63 ]. In contrast, a seven-day treatment with virgin coconut oil, high in MCT, reduced immobility in the forced swim test and was associated with reduced serum cortisol and an increase in brain antioxidants [ 64 ].…”
Section: Affective Disordersmentioning
confidence: 99%
“…There was no difference between the MCT group and the control group for the forced swim test or the social exploration test [ 62 ]. A recent study found that the acute administration of a high dose of decanoic acid increased depression/anxiety in mice during the forced swim test [ 63 ]. In contrast, a seven-day treatment with virgin coconut oil, high in MCT, reduced immobility in the forced swim test and was associated with reduced serum cortisol and an increase in brain antioxidants [ 64 ].…”
Section: Affective Disordersmentioning
confidence: 99%
“…The effect of capric acid, an MCT, was also evaluated in a study of mice subjected to behavioral tests, the results of which mimic depressive behaviors ( 133 ). An acute high dose (30 mmol/kg) and chronic low dose (0.1–3 mmol/kg) of capric acid solution were administered to mice via oral gavage.…”
Section: Major Depressive Disordermentioning
confidence: 99%
“…The apparatus was placed 400 mm above the ground, with the mice able to move freely in all directions. The EPM test was conducted in a quiet room, and the illumination level of the central area was 100 lux [46]. Each tested mouse faced the open arm and was positioned in the center of the apparatus.…”
Section: Elevated Plus Maze (Epm)mentioning
confidence: 99%